Effect of intranasal rosiglitazone on airway inflammation and remodeling in a murine model of chronic asthma - Lee, Hwa Young; Rhee, Chin Kook; Kang, Ji Young; Park, Chan Kwon; Lee, Sook Young; Kwon, Soon Suk; Kim, Young Kyoon; Yoon, Hyoung Kyu (The Korean journal of internal medicine, 2016)
Asthma is characterized by airway hyperresponsiveness, inflammation, and remodeling. Peroxisome proliferator-activated receptors have been reported to regulate inflammatory responses in many cells. In this study, we examined the effects of intranasal rosiglitazone on airway remodeling in a chronic asthma model. We developed a mouse model of airway remodeling, including smooth muscle thickening, in which ovalbumin (OVA)-sensitized mice were repeatedly exposed to intranasal OVA administration twice per week for 3 months. Mice were treated intranasally with rosiglitazone with or without an antagonist during OVA challenge. We determined airway inflammation and the degree of airway remodeling by smooth muscle actin area and collagen deposition. Mice chronically exposed to OVA developed sustained eosinophilic airway inflammation, compared with control mice. Additionally, the mice developed features of airway remodeling, including thickening of the peribronchial smooth muscle layer. Administration of rosiglitazone intranasally inhibited the eosinophilic inflammation significantly, and, importantly, airway smooth muscle remodeling in mice chronically exposed to OVA. Expression of Toll-like receptor (TLR)-4 and nuclear factor kappa-light-chain-enhancer of activated B cells (NF-κB) was increased in the OVA group and decreased in the rosiglitazone group. Co-treatment with GW9660 (a rosiglitazone antagonist) and rosiglitazone increased the expression of TLR-4 and NF-κB. These results suggest that intranasal administration of rosiglitazone can prevent not only air way inf lammation but also air way remodeling associated with chronic allergen challenge. This beneficial effect is mediated by inhibition of TLR-4 and NF-κB pathways.